Assessing long-term impact of soft drinks and acidic beverages on dental health - Alsulaimani, Abdulaziz Fareed; Irgsous, Mustafa Saoud; Aldurgham, Samar Abdulmajid; Almutairi, Yasser Mubarak; Habib, Yousef Zakaria; Mazi, Asmaa Faisal (International Journal Of Community Medicine And Public Health, 2025)
Soft drinks and acidic beverages are immensely widespread, raising questions about potential long-term effects on dental health. Their high sugar content and acidic makeup demineralize enamel, erode teeth, and increase the risk of cavities. Frequent consumption weakens tooth structure and promotes bacterial growth, which accelerates decay. Due to the extensive marketing and accessibility of these drinks, their consumption has increased, especially among younger people, raising concerns about dental health. With a focus on caries development, erosion mechanisms, and preventative measures, this review examines recent studies on the effects of these beverages. Peer-reviewed research from 2016 to 2024 was selected after a comprehensive literature search using PubMed, Web of Science, and Google Scholar. The review assesses the effects of several variables on enamel deterioration and cavity formation, including pH levels, sugar content, and frequency of consumption. Important tactics like applying fluoride, altering one's diet, and using protective coatings are being researched to reduce damage. New developments in dental care, such as protective dental coatings and remineralization procedures, are also investigated as possible ways to lessen the negative effects of acidic and soft drinks. To protect long-term dental health, the results highlight the need for greater awareness and legislative measures to support better oral hygiene practices and healthier beverage choices.